Proceedings of the Third International Conference on Bio-Inspired Models of Network Information and Computing Systems (Bionetic 2008
DOI: 10.4108/icst.bionetics2008.4713
|View full text |Cite
|
Sign up to set email alerts
|

ELASTICITY: Topological Characterization of Robustness in Complex Networks

Abstract: Just as a herd of animals relies on its robust social structure to survive in the wild, similarly robustness is a crucial characteristic for the survival of a complex network under attack. The capacity to measure robustness in complex networks defines a network's survivability in the advent of classical component failures and at the onset of cryptic malicious attacks. To date, robustness metrics are deficient and unfortunately the following dilemmas exist: accurate models necessitate complex analysis while con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…The set of networks with high robustness to random node failures has low values of average shortest path length ðhliÞ and diameter (D), and they are the most disassortative networks (r \ 0). Furthermore, it can be observed that networks with high average nodal degree ðhkiÞ show robustness to random attacks, which is in accordance with the results found in [30].…”
Section: Robustness Analysis Under Random Failures Resultssupporting
confidence: 81%
“…The set of networks with high robustness to random node failures has low values of average shortest path length ðhliÞ and diameter (D), and they are the most disassortative networks (r \ 0). Furthermore, it can be observed that networks with high average nodal degree ðhkiÞ show robustness to random attacks, which is in accordance with the results found in [30].…”
Section: Robustness Analysis Under Random Failures Resultssupporting
confidence: 81%
“…Elasticity (E): relates to the total throughput in response to the node removal [8]. The fundamental idea is to successively remove a certain fixed number of nodes r (in the original definition, r ¼ 1%) and measure the consequent throughput degradation.…”
Section: Robustness Metrics Glossarymentioning
confidence: 99%
“…Sydney et al [8] defined robustness as the "ability of a network to maintain its total throughput under node and link removal". Ali et al [3] consider a system robust, when the system is able to operate as expected in presence of uncertainties and perturbations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this more of a theoretical framework, the method remains similar: removing elements and measuring the evolution of some key properties. Endurance [24] and elasticity [25] are other attempt to understand robustness in terms of failures and how the propagate through a graph. By contrast with these work, our approach permits to finely tuned the propagation of failure for each component.…”
Section: Related Workmentioning
confidence: 99%